Jñāneśvari - Jñānadeva, fl. 1290 (SAMP early 20th-century Indian books project ;, 1909)
Commentary on Bhagavadgītā, classic work on Hindu philosophy; includes introduction dealing with the language of Jñānaśvarī and glossary of difficult words.